Spontaneous posterior vitreous detachment and chronification of migraine with aura: A case report exploring visual snow syndrome - Küster, João Guilherme Bochnia; Piovesan, Elcio Juliato (Headache Medicine, 2025)
IntroductionPosterior vitreous detachment is characterized by the separation of the vitreous humor from the retina, with its spontaneous occurrence involving photopsias and floaters. Treatment options in cases without retinal involvement are limited and observation is recommended. Migraine with aura may have visual snow syndrome as a comorbidity, with visual snow corresponding to dynamic visual changes similar to static dots.Case ReportA 57-year-old woman reported the sudden onset of complex bright flashes filling her visual field, dysmorphous multicolored rays and progressive left-sided headache of severe intensity with a pattern similar to her migraine with aura, although the visual manifestations were distinct from her typical aura presentations. Neurological examination was normal and direct ophthalmoscopy showed no retinal alterations. After complementary investigation, left posterior vitreous detachment was demonstrated with ultra-wide field retinal imaging. She maintained higher migraine frequency and intensity after the event in the following year, with the floaters being occasionally accompanied by photophobia, impaired night vision and small moving snow dots occurring in the vision of both eyes and contributing to the headache.ConclusionThis case indicates the importance of considering acute ocular abnormalities with the establishment of flashes and floaters and explores the development of secondary visual snow, an atypical clinical condition, after posterior vitreous detachment, which may be related to the chronification of the migraine.